Respuesta :

Answer:

j - 10 = 35

j = 45

Step-by-step explanation:

When it says, "less than" it means subtracting. So 10 less than j is (j - 10)

The part where is says "is" means it is equal to.

So the equation would be = (j - 10) = 35

Answer:

Equation: (j - 10) = 35

j = 45

Step-by-step explanation: Lets translate 10 less than j:

Less than means 10 is being subtracted from j.

So we can write 10 less than j as j - 10.

The word is means equal.

So, we can write is 35 as = 35.

Now lets write the whole equation toghter.

j - 10 = 35

We can also write this as 35 = j - 10.

Now we can solve for j.

Add 10 to both sides of the equation to get j by itself.

j - 10 + 10 = 35 + 10

J=45

The following equation matches this situation:

j - 10 = 35

j = 45

ACCESS MORE